The Challenges and Opportunities of E-Commerce in India: Future Prospective (International Journal of Engineering and Computer Science, 2018)
E-commerce is playing one of the vital role in business options and facilitate to explore in the future. E-commerce is concerning the paradigm shift in the business world for trading. Forecast of E-commerce is showing extraordinary prospects in business growth of Indian Economy.  The customers base of online shopping is augmented by using internet of things (IOT) and mobile phone applications. Consequently the Indian e-commerce business has seen exciting growth in since from few years. It taking into consideration India’s demographic payment system and increasing internet accessibility, the E-commerce business is growing up to greater heights. However, India’s overall retail opportunity is substantial, the online business is plagued with some critical challenges. Hence in attending current study has been carried out to depict the present condition and the future prospective of e-commerce business in India. It facilitates to analyze the present trends, explore the challenges and opportunities of e-commerce business in India.